Economic impacts of COVID-19 pandemic in Ethiopia: A review of phone survey evidence - Hirvonen, Kalle (International Food Policy Research Institute, 2020)
As in most low and middle-income countries, the paucity of timely economic data in Ethiopia makes it difficult to understand the economic impacts of the COVID-19 pandemic. To mitigate this, several organizations have launched phone surveys to gather more information about the crisis. This research report reviews the available phone survey evidence as of mid-August 2020 and identifies knowledge gaps. First, the available evidence suggest that the pandemic has not led to unusually large increases in food prices. However, a case study in the vegetable sector suggests that price dynamics are highly context and crop specific, calling for more comprehensive price monitoring to identify food value chains and areas where food price increases may have been unusually rapid. Second, employment losses have concentrated on informal sector workers while redundancies in the formal sector have been less significant. Third, there is considerable uncertainty about the income, poverty, and food security implications of this crisis. While most households report income losses, the qualitative and subjective nature of these questions mean that the magnitudes of these losses are unknown. In Addis Ababa, less subjective food security measures indicate only small negative changes in household food and nutrition security. Finally, due to limited access to mobile phones in rural areas, we have imperfect and incomplete information on how this crisis is affecting rural households.